Environmental Site Assessment of Al-Daura Refinery - Evaluation of Soil Pollution with Petroleum Products - MahmoodM. Barbooti; Adel Sharif Hamadi; Alia Abdul-Razzaq; Jinan Hussain (Engineering and Technology Journal, 2010)
The environmental site assessment (ESA) of Al-Duara refinery in Baghdad, Iraq.The hydrocarbon content of the soil around this site was measured to evaluate theextent of the organic pollution depending on selected parameters of potentialpollution. Soil samples were collected at various depths from almost all locationsincluding: production units, storage tanks, the landfill lagoons at the outside boarderof the refinery and the residence location. For the evaluation of the nature of soillayers, a monitoring well was drilled in the vicinity of a wide dumping area for heavyuntreatable materials. Some field tests were carried out to evaluate the hydrocarbonin-soil (Turbidimetric); Laboratory analysis for the soil extracts and types ofhydrocarbon pollutants. The soil texture was evaluated using the standard methods toassess any future remediation efforts. It appeared that storage tanks location is amongthe serious polluting sources via leakage or overflow of the drainage collectionchannels. The pollution sometimes extended deep in the soil, 80-100 cm. Themaintenance and rehabilitation operations contribute much pollution by heavy sludgecontaining hydrocarbons, mud and inorganic matter. Most of the pollution load isdirected towards the wastewater treatment plant. The dumping location and over morethan 30 years resulted in deep penetration of hydrocarbons so that the location isconsidered the most effective source of pollution. Finally, the fall out is a majormeans of pollution of remote area within the site by heavy hydrocarbons.Recommendations for remediation of the most polluted locations in the site werelisted at the end of this study. However, the company is continuously doing actions toremove polluted soil and replace it with clean soil.